The role of the financial feasibility study in streamlining the financing decision in banks: a Case study of a project financing request by the Bank of Agriculture and Rural Development "BADR" - Belkacemi, amira; Khouri, nabil (Journal of Research in Finance and Accounting, 2023)
This study aims to highlight the importance of the financial feasibility study of projects, in rationalizing the financing decision in banks, through a case study of a project financing request by the Bank "BADR". It became clear to us that the Bank's financing decision for the project under consideration was wrong, although the criteria of the validation conditions recorded the profitability of the project, its results were weak, which was confirmed by the sensitivity analysis of the project that recorded a negative net present value NPV (-119 974 KDA).